French cinema - Araujo, Denize; Lambach, Claudia (Curitiba, PR : Appris, 2023)
To begin, I gratefully acknowledge the support of Appris Editor for accepting the project for an E-Book, and of IAMCR - International Association for Media and Communication Research - for the Fund to Claudia Lambach, PhD, whose Post-Doctorate Project includes the organization of the E-Book and two Dossiers with FAMECOS Journal, plus two Workshops for IAMCR Conference 2023- LYON, France, online (June 26 to September 12) and face-to-face (July 9 to 13), one in Pre-Conference and another in Post-C...
Keywords: Artes performáticas; Filme